Kansas State University Human Nutrition Flexbook - Lindshield, Brian (Open textbook library., 2018)
The Kansas State University Human Nutrition (FNDH 400) Flexbook is a textbook for students taking Kansas State University FNDH 400 course.FNDH 400 is a 3-hour, intermediate-level, human nutrition course at Kansas State University take primarily by sophomores and juniors because it has prerequisites of a college biology and chemistry courses.